Mycotoxins in Zea mays, their quantification and HPLC analysis of physico-biological detoxification. Issue 22 (17th November 2022) - Murad, Maria; Ahmad, Khuram Shahzad; Iram, Shazia; Hanif, Nafeesa Qudsia; Gul, Mahwash Mahar; Elnaggar, Ashraf Y.; El-Bahy, Zeinhom M.
Abstract: Present research delves in the isolation, extraction and identification of mycotoxins from ten corn samples collected from the northern province of Pakistan. Average concentration of aflatoxin B1 and B2 by HP-TLC found in all corn samples was 27.87 and 1.35 μg/kg, respectively. Following HP-TLC, detoxification of the identified and isolated mycotoxin was performed, which was analyzed by HPLC. Screening of mycoflora exhibited Aspergillus niger and Fusarium as the most dominant fungal strains. Aflatoxin B1 was physically detoxified under UV-Lamp and direct sunlight displaying detoxification percentage of 48% and 99%, respectively. Biological detoxification involved the use of botanicals such as neem leaves, garlic and ginger powder, which portrayed an approximate detoxification of 70% from corn samples. Current research concludes that the tested physical and biological methods can be easily adopted at field and storage rooms after the harvesting of crops to avoid fungal contamination and subsequent food spoilage. Graphical Abstract: UF0001